Consumer and carer views of Australian community pharmacy practice: awareness, experiences and expectations. Issue 1 (12th December 2013) - McMillan, Sara S; Kelly, Fiona; Sav, Adem; King, Michelle A; Whitty, Jennifer A; Wheeler, Amanda J
Abstract: Objectives: To explore consumer awareness, experience and expectations of Australian community pharmacy practice, from the perspectives of consumers with chronic health conditions, carers or both. Methods: Semi-structured in-depth interviews were undertaken in four diverse regions of Australia. The constant comparison method was used for analysis purposes. Key findings: Ninety-seven interviews were conducted. Participants had limited understanding regarding the role of community pharmacy staff and the Pharmaceutical Benefits Scheme (PBS). Pharmacists were viewed primarily as medication suppliers, and the services provided by pharmacy, such as Home Medication Reviews, are predominantly unknown. Confusion still exists with respect to generic medications, medication pricing and how the PBS safety net system works. Conclusions: There is public uncertainty about specific aspects of Australian pharmacy practice. This is despite the introduction of newer professional services targeting chronic health conditions and extensive marketing campaigns involving pharmacy. If community pharmacy is to better assist consumers with chronic conditions, there needs to be improved community awareness of the professions current scope of practice and the system it works within.